Przekształcanie pamięci. Found footage jak machina kulturowej reinterpretacji - Giec, Marta (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2015)
Transforming Memory: Found Footage as a Mechanism of Cultural Reinterpretation The article is about the role of found footage in shaping the consciousness of the modern spectator in relation to historical cinematographic creations. The meaning and signifi cance of interpretation, as well as the aesthetics of experimental movies, shatter myths about classical narration and the understanding of film in its social normative role. Chosen films by Bill Morrison, Fabio Scacchioli and Peter Tscherkassky are analyzed in order to outline this issue.